"Lost in translation": Issues with the establishment of a legal market for "low risk" psychoactive products ("legal highs") in New Zealand. (4th May 2018) - Rychert, Marta; Wilkins, Chris; Witten, Karen
Abstract: Introduction: New Zealand's Psychoactive Substances Act (PSA) 2013 established the world's first regulated legal market for "low risk" psychoactive products. Aim: To explore challenges in relation to regulating the retail environment and public communication of the new policy. Methods: Semi-structured interviews with 30 key informants (KI) from the industry, government, health and NGO sectors were conducted, transcribed and analysed thematically. Results: KI overwhelmingly supported the new PSA retail restrictions, but expressed frustration about how the new regulations were managed. They questioned the effectiveness of communicating the policy to the public and media, enforcement of regulations around licenced retailers, engagement with stakeholders in local communities and the speed of developing regulations for the full regime. Many KI pointed out the reduction in the number of shops concentrated demand which increased social disruption and negative media feedback. The absence of price controls and drug education were identified as gaps in the new regime. Conclusion: Issues with the interim PSA regime highlight the significant challenges of implementing frameworks for regulated drug markets. Many issues were attributed to unrealistic timeframes, resource constraints and insufficient planning. An important task is effectively communicating the new policy to the public, engaging with local stakeholders and educating users.